Endothelial cell colonization and angiogenic potential of combined nano- and micro-fibrous scaffolds for bone tissue engineering - Santos, Marina I. (2008)
Presently the majority of tissue engineering approaches aimed at regenerating bone relies only on postimplantation vascularization. Strategies that include seeding endothelial cells (ECs) on biomaterials and promoting their adhesion, migration and functionality might be a solution for the formation of vascularized bone. Nano/micro-fiber-combined scaffolds have an innovative structure, inspired by extracellular matrix (ECM) that combines a nano-network, aimed to promote cell adhesion, with a micro-fiber mesh that provides the mechanical support. In this work we addressed the influence of this nano-network on growth pattern, morphology, inflammatory expression profile, expression of structural proteins, homotypic interactions and angiogenic potential of human EC cultured on a scaffold made of a blend of starch and poly(caprolactone). The nano-network allowed cells to span between individual micro-fibers and influenced cell morphology. Furthermore, on nano-fibers as well as on micro-fibers ECs maintained the physiological expression pattern of the structural protein vimentin and PECAM-1 between adjacent cells. In addition, ECs growing on the nano/micro-fiber-combined scaffold were sensitive to pro-inflammatory stimulus. Under pro-angiogenic conditions in vitro, the ECM-like nano-network provided the structural and organizational stability for ECs’ migration and organization into capillary-like structures. The architecture of nano/micro-fiber-combined scaffolds elicited and guided the 3D distribution of ECs without compromising the structural requirements for bone regeneration.